Gas gangrene, diabetes and amputations of upper extremities: Amputations of upper extremities - Pereira de Godoy, Jose Maria; Guerreiro Godoy, Maria de Fatima (Acta Biomedica Atenei Parmensis, 2020)
Purposes: The aim of the current study was to evaluate epidemiological data on amputations of upper extremities. Methods: The main causes of upper extremity amputations performed in the period from January 1998 to January 2008 in Hospital de Base, São José do Rio Preto were retrospectively evaluated in a descriptive and quantitative cross-sectional study. Data, including the age of the patient, gender and the reason for surgery, were obtained from hospital records identified by the international classification of diseases (ICD) code for amputation. Results: A total of 2919 amputations were performed in the period of this study with only 23 involving the upper extremities; thus 22 patients were included in this study as one was submitted to amputation of both arms. Fifteen patients (65.21%) were male with ages that ranged between 18 and 84 years old (mean = 41.6 years old). Seven patients (34.79%) were women with ages from 24 to 87 years old (mean = 58.8 years old). The causes for amputation were: accidents (14), gas gangrene (4), malignant neoplasms (3), arterial thrombosis (1) and unidentified cause (1). Conclusion: Gas gangrene of the upper extremities is associated to diabetes mellitus which highlights the severity of the disease.